ON THE PROBLEM OF BUILDINGS, STRUCTURES IN TERRITORIES WITH SOIL SUBSIDENCE - and and (Municipal economy of cities. Series: «Economy science», 2013)
Large scale dimensions and complication of the tilted building operation problem on the subsidence areas are highlighted. The information about methods of the tilted buildings leveling is given here. The offers on improving the method of the buildings leveling by soaking the subsidence soil are considered in the following article.